The Impact of Family Planning on Family Welfare - Purnamasari, Dian; Puspita, Winda Dwi; Rikhaniarti , Tri (Advances in Healthcare Research, 2025)
Purpose: This study explores the impact of family planning on family welfare, emphasizing its health, economic, and social dimensions. It aims to comprehensively understand how access to family planning services influences household financial stability, maternal and child health outcomes, educational opportunities, and women’s empowerment. The study examines barriers to the effective implementation of family planning, particularly in socio-cultural and policy contexts. Research Design and Methodology: This research adopts a Systematic Literature Review (SLR) approach, synthesizing findings from relevant studies to evaluate the effectiveness of family planning programs. The study integrates theoretical frameworks, including Human Capital Theory, to assess the long-term socio-economic benefits of family planning. Secondary data sources, including peer-reviewed journals and empirical research, were analyzed to identify key trends, challenges, and policy implications. Findings and Discussion: The findings suggest that family planning has a significant impact on reducing maternal and infant mortality rates, enhancing child health, and improving household financial security by enabling more effective resource allocation. Family planning also contributes to social mobility by increasing access to education and economic opportunities, particularly for women. However, cultural and religious barriers, unequal access to healthcare, and policy gaps remain significant challenges in achieving widespread adoption. Addressing these issues requires community-based interventions, the integration of technology, and policy reforms. Implications: The study highlights the importance of evidence-based policies in enhancing family planning services, particularly in rural and underserved communities. Governments, NGOs, and the private sector must collaborate to expand access to reproductive healthcare, integrate digital health solutions, and ensure sustainable funding. Future research should explore the role of digital technologies in increasing family planning awareness and accessibility.